Ontology Development Guide Using Protege: BCS3263SQA at FSKKP - Jessie, Ooi; Abdulgabber, Mansoor Abdullateef; Azma, Abdullah; Yee, Seng Chun (American Scientific Publisher, 2018)
Ontology is a collection of formal terms that allows the communication between a machine and humans. It contains formal naming, definitions of types, properties and interrelations within a specific domain. Ontology allows knowledge visualisation of selected domain. However, developing an ontology requires a huge effort including designing its structure and the actual ontology development process. Software Quality Assurance (SQA) is a process that assure the reliability of a software and reduce its maintenance effort. Therefore, it is important for a computer science students to have a basic understanding on every aspect of SQA process. However, to master the SQA is a challenging task due to its wide coverage in the subject. To improve the learning process of the students in Universiti Malaysia Pahang, an ontology has been developed to provide an overview about the structure of the courses and help the students to visualise the entire course structure. In this paper, we discussed about the steps require for developing an ontology using Protégé. We focus on the ontology development methodology and how to use Protégé as an ontology development tools. As the result of the SQA ontology development, there are 5 classes and 40 terms. These terms help SQA class’s students in understanding the entire course structure.